Deleterious Biological Effects of Endocrine Disruptors: An Insight into Human Health Risks - Lawati, Abdullah A.; Hashmi, Lubna Al; Aswami, Husain Al; Hadhrami, Abdulrahman Al; Chin, Kok-Yong; Sirasanagandla, Srinivasa Rao; Das, Srijit (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Endocrine-disrupting chemicals (EDCs) are environmental pollutants. Since EDCs are present in various consumer products, contamination of human beings is very common. EDCs have deleterious effects on various systems of the body, especially the endocrine and reproductive systems. EDCs interfere with the synthesis, metabolism, binding, or cellular responses of natural estrogens and alter various pathways. Biological samples such as blood, saliva, milk, placental tissue, and hair are frequently used for biomonitoring and the detection of EDCs. Early detection and intervention may help in preventing congenital anomalies and birth defects. The common methods for determining the presence of EDCs in body fluids include gas chromatography, high-performance liquid chromatography, and mass spectrometry. Understanding the health effects and dangers of EDC is important, given their widespread use. This mini-review aims to summarize the adverse biological effects of several important classes of EDCs and highlights future perspectives for appropriate control.
Keywords: environment